A Deep Learning Approach for Mild Depression Recognition Based on Functional Connectivity Using Electroencephalography - Li, Xiaowei; La, Rong; Wang, Ying; Hu, Bin; Zhang, Xuemin (Frontiers in Neuroscience, 2020)
Early detection remains a significant challenge for the treatment of depression. In this study, we proposed a novel approach to mild depression recognition using electroencephalography (EEG). Firstly, we explored abnormal organization in the functional connectivity network of mild depression using graph theory. Secondly, we proposed a novel classification model for recognizing mild depression. Considering the powerful ability of CNN to process two-dimensional data, we applied CNN separately to the two-dimensional data form of the functional connectivity matrices from five EEG bands (delta, theta, alpha, beta, and gamma). In addition, inspired by recent breakthroughs in the ability of deep recurrent CNNs to classify mental load, we merged the functional connectivity matrices from the three EEG bands that performed the best into a three-channel image to classify mild depression-related and normal EEG signals using the CNN. The results of graph theory analysis showed that the brain functional network of the mild depression group had a larger characteristic path length and a lower clustering coefficient than the healthy control group, showing deviation from the small-world network. The proposed classification model obtained a classification accuracy of 80.74% for recognizing mild depression. The current study suggests that the combination of a CNN and functional connectivity matrix may provide a promising objective approach for diagnosing mild depression. Deep learning approaches such as this might have the potential to inform clinical practice and aid in research on psychiatric disorders.